Do problematic gamblers and loot boxers share similar fallacies of thought? A comparative analysis of cognitive biases - Sanmartín, Francisco J.; Velasco, Judith; Gálvez-Lara, Mario; Cuadrado, Fátima; Moriana, Juan A. (Frontiers in Psychology, 2024)
Cognitive biases are associated with the beginning and maintenance of addictive behaviours. While these biases have been studied in gambling, they have yet to be thoroughly investigated in the context of loot boxes (LBs), largely because of the relatively recent emergence of this phenomenon. This study compared cognitive biases in problematic gamblers, non-problematic gamblers, LB purchasers, and free-LB openers. For this aim, 279 participants (63.1% males) with a mean age of 23.65 years (SD = 8.66) completed a self-report. The results showed no differences between problematic gamblers, LB purchasers and LB openers on illusion of control and predictive control. In contrast to LB openers, problematic gamblers and LB purchasers obtained statistically similar scores on interpretative biases, gambling-related expectancies and the total score of the Gambling Related Cognitions Scale (GRCS). Only problematic gamblers experienced a higher perceived inability to stop gambling. Moreover, problematic gamblers, LB purchasers and LB openers scored higher on all biases compared to non-problematic gamblers. Eighty-six participants simultaneously gambled and used LBs. When this overlap was controlled, problematic gamblers and loot boxers shared all cognitive biases but the perceived inability to stop gambling; and scored statistically higher than non-problematic gamblers in all cognitive biases except for the illusion of control. The study provides additional evidence of the relationship between gambling and LBs.